Effect of Pupil Dilation with Tropicamide on Retinal Vascular Caliber. (2nd November 2019) - Frost, Shaun; Gregory, Cynthia; Robinson, Liam; Yu, Shuang; Xiao, Di; Mehdizadeh, Maryam; Burnham, Samantha; Dehghani, Cirous; Vignarajan, Janardhan; Kanagasingam, Yogesan; Schlaich, Markus P.; Prentice, David
ABSTRACT: Purpose : The retinal blood vessels reflect changes in the brain's micro-circulation and these changes have been shown to correlate with the incidence of diseases such as stroke, heart disease and Alzheimer's disease. Studies investigating the retinal vasculature routinely use pupil dilation with tropicamide to optimize image acquisition and quality. The aim of this study was to investigate the effects of tropicamide on retinal vascular parameters using retinal photography. Methods : The study was performed on 41 healthy young subjects of both sexes, using tropicamide to dilate only the right pupil, leaving the left as a control. Results: Pupil dilation with tropicamide resulted in reduced retinal vessel width measures based on standardized approaches, particularly reduced arteriolar caliber ( p < .0005). However, closer investigation of the images revealed reduced fundus image magnification in the post-tropicamide images, based on reduced optic nerve head diameter ( p < .0005) and longitudinal analysis with image registration and affine transformation ( p < .0001). No change in vessel width parameters was observed after adjustment for image magnification. Conclusion: These results suggest that tropicamide does not change the width of the retinal vessels, however width parameters as measured by standard approaches may be reduced due to image magnification changes resulting from cycloplegia. In this study, improved optic nerve head segmentation for image scale conversion removed the magnification error. With this correction, the tropicamide intervention had no effect on vessel width parameters in young healthy people and could be utilized in future without affecting the results of retinal vascular analysis.